New Insights on the Effect of Forced Laser-Etched Nucleation on the Unsteady Evolution of Two-Phase Flow in a Beer Glass - Beaumont, F.; Bogard, F.; Murer, S.; Polidori, G. (Experimental Techniques, 2023)
This study investigated the influence of the number of nucleation sites on the evolution of the dissolved CO2 concentration of beer contained in an etched glass comprising 0 to 70 etchings. Four identically shaped glasses were studied, three etched and one non-etched. We followed the temporal evolution of the liquid (i.e., beer) and gaseous (i.e., CO2) phases of the beer for each of them. The gaseous phase is monitored by measuring the evolution of the dissolved CO2 concentration in the beer once poured into the glass. Particle image velocimetry (PIV) techniques are used to quantify the mixing dynamics of the beer during the tasting. The results show that the CO2 concentration decreases approximately 3.7 times faster in the glass with 70 etchings than in the unetched glass. This study suggests a close link between the number of nucleation sites and the release of dissolved CO2 by different mechanisms: bubble bursting, molecular diffusion, and mass convection-diffusion, the latter being increased by liquid mixing mechanisms. On the one hand, too many bubbles will bother the consumer by causing a chemical sting and will quickly deplete the beer in dissolved gas. On the other hand, too few bubbles will not allow conveying the aromas to the surface and the consumer will judge the beer as too bland and not visually flattering, hence the need to find a compromise.
Keywords: CO2; Convection; Molecular diffusion; Nucleation; PIV